Mobile testing : an ASTQB-BCS foundation guide - Black, Rex, 1964- (BCS Learning and Development, 2018)
Mobile testing is the process of testing the functionality, usability and consistency of mobile software. While similar to standard software testing, efficient and effective mobile testing requires an additional set of skills on top of those usually required by software testers. With this essential guide, in line with the ASTQB Certified Mobile Tester syllabus, you will gain the understanding and skills you require to begin your journey to becoming a proficient mobile tester. -- 'Rex Black's Mobile Testing book, based on the ASTQB Certified Mobile Tester Syllabus, puts mobile testing techniques and concepts into perspective using real world examples. Not only is this book informative on the theory behind successful mobile testing, but his ability to relate these back to situations in which he has personally experienced assists the reader in gaining a greater understanding. All techniques and concepts in this book are well explained and relatable, making the transition and advancement in mobile testing much easier. Whether you are looking at gaining your ASTQB Mobile Tester Certification, or just looking at learning or improving your skills in mobile testing, this book is definitely one to read and keep in your toolkit.' Marie Walsh, Change and Release Manager, FIIG Securities and ANZTB Board Member -- 'Rex's book on mobile testing is not only very helpful but also amusing in its application of short, understandable real-life examples. I wish mobile app makers could have read it years ago.' Istvan Forgacs, CEO, 4Test-Plus and co-author of 'Agile Testing Foundations'